Physical Geology - Longwell, Chester R.; Knopf, Adolph; Flient, Richard F. (New York : Wile, 1948)
Weathering and its part in erosion, waste of resources, running water, lakes and swamps, glaciers and glaciation, wind erosion and deposition, volcanoes and volcanism, the origin and history of mountains, earthquakes.
This record contains unverified, old data from shelflist card.
Pamphlet copyrighted 1948.
Slides are in cardboard proj. mounts, with captions in accompanying pamphlet.
Keywords: Physical Geology